Decomposition of maize stover varies with maize type and stover management strategies: A microcosm study on a Black soil (Mollisol) in northeast China. (15th March 2019) - Liu, Siyi; Fan, Ruqin; Yang, Xueming; Zhang, Zhenhua; Zhang, Xiaoping; Liang, Aizhen
Abstract: Crop residue decomposition has an important impact on soil organic carbon (SOC) sequestration and CO2 emission. Residue quality and management strategies are two important factors regulating decomposition process and SOC mineralization and greenhouse gas emission. In this study, a microcosm experiment in field condition was conducted on a silty loam (a Black soil) in Northeast China to investigate stover decomposition and soil CO2 emission characteristics as influenced by different crop cultivars and stover field incorporation methods. Stover from two popular maize cultivars Xianyu335 (XY) and Liangyu99 (LY) were applied in two modes (soil surface application vs soil incorporation) at a rate of 11 t ha −1, and CO2 efflux was monitored during the decomposition duration of 144 days. The structural transformation of carbon functional groups in maize stover were evaluated using solid state 13 C-CPMAS NMR and elemental analysis techniques. Results showed that up to 71.7%∼86.9% (weight basis) of C and N in soil-incorporated stover was decomposed during the study period, which was significantly greater than the losses (32.8%∼55.3%) of C or N from the surface-applied stover for both maize cultivars; decomposition rates of main C functional groups were significantly higher in soil incorporation (71.1%∼88.8%) than in surface application (20.9%∼60.2%) systems. The concentrations of SOC, total N, available N, and microbial biomass C and N in soil were also higher with stover incorporation than surface application. Stover incorporation resulted in a notably lower CO2 emission rate and accumulative CO2 efflux (53.9–55.4 mol m −2 ) during the stover decomposition compared with surface application (57.4–67.0 mol m −2 ). Between the two maize cultivars, the LY stover showed a higher decomposition rate and greater capacity for SOC sequestration when incorporated into soil. The LY stover induced higher (16.8%) CO2 emission than XY when applied on soil surface, but no significant difference was found between the two cultivars when incorporated into soil. The results suggested that cultivar selection and stover management strategies have great potential in reducing soil CO2 emission while improving soil biochemical properties. Incorporating the LY stover into soil rather than surface mulching could enhance SOC sequestration and reduce CO2 emission. Highlights: Soil CO2 emission varied with maize cultivar when stover was surface-applied. Stover decomposition process and soil C and N were greatly affected by maize cultivar. Stover decomposition rate was higher with soil incorporation versus surface application. Stover incorporation resulted in lower CO2 emission and higher soil C and N retentions. Proper cultivar and stover managements reduce soil CO2 efflux and favor C sequestration.